Advancing research to eliminate mental illness stigma: an interventional study to improve community attitudes towards depression among university students in Singapore - Goh, Janrius Chong Min (2022)
Background: After decades of anti-stigma initiatives, the Advancing Research To Eliminate Mental Illness Stigma (ARTEMIS) intervention study is one of the first in Singapore to evaluate the effects of an anti-stigma intervention on attitudes towards depression in university students. Methods: 390 university students from a local university in Singapore were voluntarily recruited for the study. The ARTEMIS intervention comprises an educational and social contact component, as well as a question and answer (Q&A) session with experts in the area of mental health. The Community Attitudes towards Mental Illness (CAMI) scale was administered at baseline, post-intervention and at 3-months follow-up. A confirmatory factor analysis (CFA) was conducted. Results: The CFA identified a 3-factor model for the CAMI with a decent fit (RMSEA = 0.06, CFI = 0.93, TLI = 0.93, SRMR = 0.06). Favourable shifts in attitudes across the factors were observed immediately after the intervention (p < 0.001). Gender (β = − 1.19, 95% CI: − 2.10, − 0.27, p = 0.01) and nationality (β = − 1.23, 95% CI: − 2.35, − 0.11, p = 0.03) were identified as significant correlates for the community mental health ideology (CMHI) factor. Linear effects indicated that having a close social contact with mental illness observed a smaller decrease in authoritarianism scores from pre- to post-intervention (β = 0.85, 95% CI: 0.18, 1.53, p = 0.01); whereas quadratic effects found a greater decrease in scores from post-intervention to after 3-months for benevolence (β = − 0.34, 95% CI: − 0.52, − 0.16, p < 0.001) and CMHI (β = − 0.22, 95% CI: − 0.45, − 0.002, p = 0.048). Conclusion: The anti-stigma intervention shows promising short-term results across the CAMI dimensions even after adjusting for sociodemographic correlates. However, the intervention did not observe the sustained attitude shifts after 3-months. Recommendations for future anti-stigma interventions were also considered.